Extrarenal nephroblastoma in a 7 year old child: a rare case report with review of literature - Kumar, Sasi; Sunilkumar, Menon Narayanankutty; Surendran, Divya (International Journal of Contemporary Pediatrics, 2017)
Nephroblastoma or Wilms’ tumors are a tumour of the kidney and is the commonest primary malignant tumour occurring in childhood with classic histopathological features. Majority of these tumors present as renal masses and atypical presentations like extrarenal masses have also been known. Extrarenal Wilms’ tumor or Nephroblastoma (ERWT), excludes primary tumor in the kidney, is extremely rare and occurs predominantly in children. Most of the cases that have been reported involved the retroperitoneum. It is generally located anywhere in the retroperitoneum from the nephric region down through lumbar, iliac, pelvic region to inguinal canal. Though there are reports regarding its prevalence, its occurrence is very rare in childhood. We are reporting a case of ERWT in a 7 year old child arising from the retroperitoneum, adherent to the ascending colon, second and third part of duodenum, right kidney and ureter.